Крымские страницы жизни выдающегося кардиохирурга современности – Лены Николаевны Сидоренко - Сухарева, Г.Э. (Таврический медико-биологический вестник, 2013)
статті наводяться факти біографії, зокрема кримський період життя, видатного кардіохірурга
сучасності – Олени Миколаївни Сидоренко. The facts of biography are presented in the article, in particular the Crimean period of life, prominent cardio
surgeon of contemporaneity – Helen Nick Sidorenko.